The Effect of Tenants Housing Cost Burden on Household Economic Hardship in Turkey - Bulut, Emir; Acar Balaylar, Nilgün; Üçdoğruk Birecikli, Şenay (International Journal of Contemporary Economics and Administrative Sciences, 2023)
The aim of this study is to contribute to the poverty literature in Turkey by associating the serious economic difficulties experienced by the tenants with the burden of housing costs. Housing costs, which are an important expenditure item for households, reduce non-housing expenditures such as health, education, food, and clothing, and thus cause serious economic difficulties for households. The empirical analysis relies on data derived from the TURKSTAT Income and Living Conditions Survey (ILCS) micro data set for 2021. We limited our research to tenants aged 15 and over who are in the respondent of the household. We first worked with the probit model to understand the impact of actual and perceived housing cost burdens on household economic difficulties. In the following part, We worked with ordered probit models to determine the probability of households being unable to pay their electricity and water bills, rent, interest-bearing debts, or housing loans as planned in the last 12 months, and finally being unable to meet their total expenditures with their total income. We acted with the hypothesis that those responsible for households who have heating problems due to insulation are unemployed (or not working), have health problems, are single, have a low education level, and have a low income are traditionally included in the disadvantaged categories. Our findings indicate that as housing expenses increase, the probability of households experiencing severe economic difficulties also increases. As housing costs rise, individuals are more likely to be unable to pay their rent, energy, and water bills once or twice a year. The excessive increase in housing and rental costs in Turkey in 2022 has further exacerbated the economic hardships faced by impoverished individuals. Consequently, the findings from 2021 imply that the severity of economic hardships will continue to increase in the coming years.